ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK RAKYAT INDONESIA (BRI) SEBELUM DAN SETELAH TERDAMPAK COVID-19 MENGGUNAKAN METODE CAMELS DAN RGEC - Evi Noviani; Yeni Somantri (LP2M Universitas Perjuangan Tasikmalaya, 2021)
The health level assessment used in this study is the CAMELS method and the RGEC method. This study aims to analyze the difference in the level of bank soundness between before and after being affected by COVID-19. The research method used in this study is a comparative descriptive with a quantitative approach, the sample in this study is the quarterly financial report of Bank Rakyat Indonesia for the 2019-2020 period. This research is a research with secondary data. This study uses descriptive statistical analysis, normality test, paired sample t-test. The results show that there are significant differences in the assessment of the soundness of banks using the CAMELS method with the ratio of Capital Adequacy Ratio, Net Profit Margin, Net Interest Margin and RGEC Method which uses the ratio of Operating Expenses to Operating Income, Net Interest Margin, Capital Adequacy Ratio.